PEMANFAATAN ICT DALAM PEMBELAJARAN - Ace Suryadi (LPPM Universitas Terbuka, 2007)
The conventional instruction which is characterized by, for example, seperating schools from their environments, teachers as the only source of knowledge and quiet learning classrooms is no more effective and even hampers the development of student’s potentials. The concept of multiple intelligences and the new finding of human brain’s stratified structure implies a new alternative of instruction in order to bring schools and the educational system in line with new era’s up to date demands. The alternative involves the reform of instructional approach and the information and communication technology (ICT) for education. The school reform must be taken in the context of the education reform